Pengujian Vigor Daya Simpan dan Vigor terhadap Kekeringan pada Benih Padi Gogo dan Padi Sawah - Feni Shintarika; Faiza Chairani Suwarno; . Suwarno (Departemen Agronomi dan Hortikultura, 2013)
The objectives of the study were to evaluate seed storability and vigor to drought of rice genotypes from different ecologies and correlation among the characters. The experiments were conducted in the Seed Science and Technology Laboratory, Bogor Agricultural University from April to August 2011. Duration of rapid aging using ethanol vapour for testing seed storability were 87.6 and 155.4 minutes for upland and lowland rice seeds respectively. The rolled paper methods with Polyethylen Glycol (PEG 6000) at -2.0 bar was used for testing seed vigor to drought. Rice seed of 40 genotype consisting of 20 upland and 20 lowland were evaluated using Randomized Block Design with three replications. There were no correlation between seed storability and vigor to drought on all genotypes, and no similiarity of those characters on the best five genotypes. Genotypes with the highest storability were B12154D-MR-22-8 for upland rice and Aek Sibundong for lowland. Genotypes with the highest vigor to drought were B12165D-MR-8-1 and B12161D-MR-1-4-2 for upland rice, B12672-MR-19-2-PN-1-3 and Aek Sibundong for lowland.Keywords : drought stress, Rapid aging